The role of skin self-examination at the Swiss skin cancer day - Badertscher, Nina (BMC Health Serv Res, 2014)
BACKGROUND: The rising incidence of melanoma – Switzerland has the highest incidence in Europe - is a major public health challenge. Swiss dermatologist introduced the “Swiss Skin Cancer Day” (SSCD) in 2006, which provides skin cancer screening at no costs. The aim of the study was to describe the participating subjects and their motivation and investigate factors influencing the probability of a clinical diagnosis of skin malignancy. METHODS: 150 dermatologists were involved in the SSCD in May 2012. Dermatologists were not remunerated. Participants had the opportunity to show a single skin lesion to a dermatologist at no cost. A questionnaire for each participating subject collected data about subjects’ age, sex, risk factors and reason for encounter; furthermore the dermatologist noted down clinical diagnosis and further management. We used descriptive statistics to report characteristics of participants and skin lesions. We built two multiple logistic regression models, one regarding the clinical diagnosis of skin malignancy and one regarding the further management. RESULTS: 5266 subjects (55.6% female) were assessed; in 308 (5.8%) participants a clinical diagnosis of skin malignancy was found. In 1732 participants (32.9%) a clinical follow up or an excision was recommended. In the multiple logistic regression model age, sex, skin phototype and the reason for participation at the SSCD were found as significant risk factors regarding the clinical diagnosis of skin malignancy. Participants with skin cancer risk factors were more likely to get a clinical follow up recommended even if the clinical diagnosis was benign. CONCLUSION: A self-perceived suspicious lesion was the strongest predictor for a clinical diagnosis of skin malignancy at the SSCD. This suggests that skin self-examination might also work in general population. Future research should focus on better access to a specialist in case a suspicious skin lesion was discovered. Safety and quality of the SSCD should be further investigated, especially concerning the discrepancy between the low number of malignant lesions and the high quantity of participants where further clinical examinations or interventions were recommended. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12913-014-0581-6) contains supplementary material, which is available to authorized users.